Research on machining compacted graphite iron under oil-on-water cooling and lubrication conditions based on modified material model - Ding, Feng; Wang, Chengyong; Lin, Haisheng; Li, Suyang; Zheng, Lijuan; Wang, Qimin (International journal of advanced manufacturing technology, 2019)
Oil-on-water (OoW) techniques, including external OoW sprayed to both the rake face and flank face (EOoW rf ), as well as cryogenic air mixed with OoW (CAOoW), improve the machinability of compacted graphite iron (CGI). This paper proposes a modified material model for RuT400 CGI cutting, based on flow softening and weak thermal softening effect, as observed during split-Hopkinson pressure bar tests. Employing a modified material model and Cock-Latham damage model, a thermo-mechanical coupled finite element (FE) model, for RuT400 cutting, is presented. The simulations, considering dry cutting, EOoW rf , and CAOoW, are conducted for the purpose of revealing the causes for the RuT400 difficult-to-cut property and for establishing how the mechanism of OoW can improve cutting performance. The results show that the effective stress, required to form chip segments in RuT400 machining, is much lower than in hardened steel, so RuT400 is more likely to form a serrated chip. In dry cutting, the chip bottom surface is subject to high strain and temperature, leading to the work-material phase transformation, followed by aggravating adhesive and abrasive wears. Although EOoW rf has little influence on chip morphology and effective stress, it reduces the temperature and strain on chip bottom surface by reducing friction, thus suppressing the occurrence of phase transformation. Due to low friction and high heat exchange, CAOoW produces the lowest tool-chip interface temperature and minimal adhesive wear. For high-speed cutting of RuT400, compared to dry cutting, EOoW rf and CAOoW can effectively reduce cutting forces and maintain the tool temperature in a lower range, where low friction on tool-chip interface plays a key role. The proposed FE model can be used in the future to improve CGI’s machinability, by changing cooling parameters, tool geometry/material, and other machining variables.